Seed abortion in the bat pollinated Neotropical tree species, Caryocar brasiliense (Caryocaraceae) - Collevatti, Rosane G; Estolano, Raquel; Garcia, Silmara F; Hay, John D (Botany, 2009)
In self-compatible plants, the reduction in brood size may be caused either by inbreeding depression, resource limitation, maternal regulation of offspring quality, or by sibling rivalry. We studied seed abortion in Caryocar brasiliense Camb. (Caryocaraceae), a Neotropical tree species, to verify whether seeds sired by self-pollination are aborted. Fruits were sampled from 23 mother trees to estimate seed set and proportion of aborted seeds. Ripened and aborted seeds from 18 mother trees were genotyped using 10 microsatellite loci together with mother trees and all nearby adults (83 adults) to determine the pollen donor by assignment test. From the 541 seeds, 190 were aborted and the mean number of aborted seeds per fruit was 0.627 (SD = 0.807). Proportion of aborted seeds was different among mother trees and among fruits within mother trees. All but three aborted seeds were sired by self-pollination and selfed seeds were aborted in fruits harbouring both selfed and outcrossed seeds. Aborted outcrossed seeds were sired by pollen donors closely related to mother trees. Our results strongly support that seed abortion in C. brasiliense may be the outcome of inbreeding depression and sibling rivalry when selfed and outcross pollinated ovules compete.